How does breeding system variation modulate sexual antagonism? - Bedhomme, Stéphanie; Bernasconi, Giorgina; Koene, Joris M.; Lankinen, Åsa; Arathi, H. S.; Michiels, Nico K.; Anthes, Nils (My University, 2009)
The study of sexually antagonistic (SA) traits remains largely limited to dioecious (separate sex), mobile animals. However, the occurrence of sexual conflict is restricted neither by breeding system (the mode of sexual reproduction, e.g. dioecy or hermaphroditism) nor by sessility. Here, we synthesize how variation in breeding system can affect the evolution and expression of intra- and inter-locus sexual conflicts in plants and animals. We predict that, in hermaphrodites, SA traits will (i) display lower levels of polymorphism; (ii) respond more quickly to selection; and (iii) involve unique forms of interlocus conflict over sex allocation, mating roles and selfing rates. Explicit modelling and empirical tests in a broader range of breeding systems are necessary to obtain a general understanding of the evolution of SA traits.
Keywords: sexualconflict; sexallocation; selfing; sex chromosomes; simultaneoushermaphroditism; dioecy